Modified Model to Calculate Low Earth Orbit (LEO) for A satellite with Atmospheric Drag - H.S. Almohammadi, Abdulrahman (Iraqi Journal of Science, 2023)
In this paper, the satellite in low Earth orbit (LEO) with atmospheric drag perturbation have been studied, where Newton Raphson method to solve Kepler equation for elliptical orbit (i=63 , e = 0.1and 0.5, Ω =30 , ω =100 ) using a new modified model. Equation of motion solved using 4th order Rang Kutta method to determine the position and velocity component which were used to calculate new orbital elements after time step ) for heights (100, 200, 500 km) with (A/m) =0.00566 m2/kg. The results showed that all orbital elements are varies with time, where (a, e, ω, Ω) are increased while (i and M) are decreased its values during 100 rotations.The satellite will fall to earth faster at the lower height and width using big values for eccentricity (e) and (A/m) ratio. Were the results got lifetime at height = 200, e = 0.1 equal 11 days for A/m =0.02 m2/kg, while satellite's lifetime at height = 200, e = 0.1 for A/m = 0.09 m2/kg equal 6 days.